2009
DOI: 10.1002/adfm.200901358
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Triggered Self‐Assembly of a Spiropyran‐Functionalized Dendron into Nano‐/Micrometer‐Sized Particles and Photoresponsive Organogel with Switchable Fluorescence

Abstract: The synthesis, self‐assembly, and spectroscopic investigations of spiropyran (SP)‐functionalized dendron 1 are reported. Under UV light irradiation, assembly of 1 into nano‐/microparticles occurs due to the transformation of the closed form of SP into the open merocyanine (MC) form. The formation of these nano‐/microparticles is confirmed by transmission electron microscopy (TEM) and dynamic light scattering (DLS) experiments in addition to the confocal laser scanning microscopy (CLSM) measurements. These nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
75
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(78 citation statements)
references
References 61 publications
3
75
0
Order By: Relevance
“…Previous work on spiropyran photochromic systems include their use for photo-induced optical sensing of metal ions, continuous flow optical sensing of solvents of different polarity [23,24], reversible photo-actuators for microfluidic applications [25][26][27], photo-chemopropulsion of microdroplets [28], and self-assembly [29,30], among others. More recently it was demonstrated that the conversion between the SP and MC form can be achieved also mechanically under tensile loading, showing the capability to create mechanochromic materials using SP containing polymers [31].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on spiropyran photochromic systems include their use for photo-induced optical sensing of metal ions, continuous flow optical sensing of solvents of different polarity [23,24], reversible photo-actuators for microfluidic applications [25][26][27], photo-chemopropulsion of microdroplets [28], and self-assembly [29,30], among others. More recently it was demonstrated that the conversion between the SP and MC form can be achieved also mechanically under tensile loading, showing the capability to create mechanochromic materials using SP containing polymers [31].…”
Section: Introductionmentioning
confidence: 99%
“…This caused spontaneous association of MC in order to minimize the overall energy of the system. 13,16,17 In the case presented here however, these conditions are not satisfied, no spontaneous association is observed, and the turbidity of the solution exhibits good homogeneity (ESI, † Fig. S2).…”
mentioning
confidence: 97%
“…through the carboxylic acid group) and between MC-COOH molecules and water. 9,16,18 Our studies suggest that the microstructures obtained present photochromic properties not only at the liquid/air interface (ESI, † Fig. S11), but also in the solid state, see Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it remains a great challenge to date in the design of effective dendritic organogelators with no conventional gelation motifs such as peptide and long alkyl chains [22,23]. We previously reported a series of peripherally dimethyl isophthalate-functionalized poly(benzyl ether) dendrons, which could act as a highly efficient dendritic organogelator despite the lacking of any conventional gelating motifs [24,25]. The multiple strong - stacking interactions due to the peripheral dimethyl isophthalate motifs and non-typical hydrogen bonding were found to be the key contributor in forming the self-assembled gel.…”
mentioning
confidence: 99%